Advances in Food, Bioproducts and Natural Byproducts for a Sustainable Future: From Conventional to Innovative Processes - Garcia-Garcia, Isidoro; Simal-Gandara, Jesus; Gullo, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The world population is expected to reach almost 10,000 million in 2050, so, it is necessary to use our resources efficiently: to produce more food using less land and pollute less, to optimize the production and use of biomass from diversified resources. For this, new approaches and processes, with special emphasis from a biotechnological perspective, may need to be implemented to move towards a circular model that will confer environmental sustainability. In this book, the analysis and optimization of some examples of food and bioproduct processes, as well as development of innovative and emerging food and byproducts processing methods, are considered. Valorization, bioprocessing, and biorefining of food-industry-based streams, the role of industrial microorganisms, the isolation of high added-value compounds, applications of the resulting bio-based chemicals in food manufacturing, novel food formulations, among others, are addressed.